2019
DOI: 10.11646/phytotaxa.387.2.2
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>DNA Barcoding of Endangered <em>Paphiopedilum </em>species (Orchidaceae) of Peninsular Malaysia</strong></p>

Abstract: In this study, the efficacy of four DNA markers and their combinations (rbcL, matK, ITS, trnH-psbA) as barcode markers were tested across the endangered Paphiopedilum species from Peninsular Malaysia. Four species of Paphiopedilum were sampled and barcoded. The DNA barcodes reliabilities were evaluated using NCBI BLASTn program, phylogenetic tree via Neighbour-Joining method with 1000 bootstrap replicates in MEGA 6 and barcoding gap assessment. matK is the most promising barcode with high sequence quality (100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…The remaining 33 samples showed a similar percentage of 99,0% in comparing to Genbank (DQ464235.1 and AJ133896.1) as indicated in Table 1. Our obtained results were similar to some previous studies to use rbcL to identify the higher taxonomic levels [23][24]. As the results attained, it demonstrated that 35 samples collected from different geographical provinces were accurately the Huperzia species.…”
Section: Molecular Markers Application To Identify Huperzia Samples Bsupporting
confidence: 90%
“…The remaining 33 samples showed a similar percentage of 99,0% in comparing to Genbank (DQ464235.1 and AJ133896.1) as indicated in Table 1. Our obtained results were similar to some previous studies to use rbcL to identify the higher taxonomic levels [23][24]. As the results attained, it demonstrated that 35 samples collected from different geographical provinces were accurately the Huperzia species.…”
Section: Molecular Markers Application To Identify Huperzia Samples Bsupporting
confidence: 90%
“…Although matK was proposed as the best barcode, with 100% resolution in two previous Paphiopedilum studies [28,41], our study agreed with Parveen et al (2017), who found that denser sampling decreased the resolution of matK [42]. However, the combination of matK with another locus was recommended as well.…”
Section: Genetic Diversity and Identification Of The Paphiopedilum Posupporting
confidence: 78%
“…Although low-copy nuclear genes were not included in this study, the authors recommended the use of these regions in the DNA barcoding of this genus for more precise identification [45]. Recently, Rajaram et al (2019) worked on four Paphiopedilum species of Peninsular Malaysia for discriminatory power using rbcL, matK, ITS, and trnH-psbA loci. In that study, matK was also shown to have the highest capability of resolution (100%) [28], as described by Parveen et al (2012) [41].…”
Section: Introductionmentioning
confidence: 99%
“…The matK sequences discriminate the closely related P. barbatum and P. callosum var. sublaeve, therefore supporting the species circumscription by Cribb (1998) (Rajaram et al 2019). Nevertheless, slipper orchids are infamously variable, and unusual plants may sometimes be natural hybrids, especially when the putative parents grow sympatrically (Averyanov et al 2007, Leong 2014, van der Ent et al 2015.…”
Section: Introduction Paphiopedilum Originates From Thementioning
confidence: 77%
“…P.J.Cribb belong to subgenus Paphiopedilum (Seidenfeiden & Wood 1992, Cribb 1998, Leong 2014. A work on DNA Barcoding of Endangered Paphiopedilum species of Peninsular Malaysia using four DNA barcode loci and their combinations (rbcL, matK, ITS, trnH-psbA) published by Rajaram et al (2019) clusters each species as a monophyletic clade. The matK sequences discriminate the closely related P. barbatum and P. callosum var.…”
Section: Introduction Paphiopedilum Originates From Thementioning
confidence: 99%